Housing Policy in the Highly Competitive City: Case Studies of London and New York - Maglumtong, Montouch; Maglumtong, Medhas; Leebamroong, Chana (Journal of Faculty of Architecture and Design RMUTP, 2024)
This article aims to analyze the policy and implementation of housing development in the highly competitive city of London, UK and New York City, USA. This is a qualitative research that used document collection along with surveys, observations, and photography of case studies by the researcher and interviews with housing development experts to verify the accuracy of information. The results of the study showed that the two cities had common housing policies, which are; amending the law to be flexible in order to facilitate the development of affordable housing; creating cooperation at all level (communities, government, private sector, and charitable organizations); consideration of socially vulnerable groups (the elderly, the homeless, and the disabled); inclusive development; and creating diversity in the neighborhood by mixing income groups in each project. This led to the enhancement of urban competitiveness in terms of improving the quality of life of the population, which was the foundation of human resource development. It was also the direct responsibility of the government to provide affordable housing for all in the city, which will become a driving force that helps support cities to have higher competitiveness.